Association Between Gut Microbiota and Autism Spectrum Disorder: A Systematic Review and Meta-Analysis - Xu, Mingyu; Xu, Xuefeng; Li, Jijun; Li, Fei (Frontiers in Psychiatry, 2019)
Autism spectrum disorders (ASD) are characterized by stereotyped behavior and deficits in communication and social interactions. Gastrointestinal (GI) dysfunction is an ASD-associated comorbidity, implying a potential role of the gut microbiota in ASD gastrointestinal pathophysiology. Several recent studies found that autistic individuals harbor an altered bacterial gut microbiota. In some cases, remodeling gut microbiota by antibiotics administration and microbiota transfer therapy reportedly alleviate the symptoms of ASD. However, there is little consensus on specific bacterial species that are similarly altered across individual studies. The aim of this study is to summarize previously published data, and analyze the relative abundance alteration of bacterial genera in gut microbiota in control and ASD individuals using meta-analysis. We analyzed nine studies including 254 ASD patients and found that children with ASD had lower percentages of Akkermansia, Bacteroides, Bifidobacterium, Parabacteroides, and a higher percentage of Faecalibacterium in the total detected microflora compared with control individuals. In contrast, the children with ASD had lower abundance of Enterococcus, E. coli, Bacteroides, Bifidobacteriums, and higher abundance of Lactobacillus. This meta-analysis suggests an association between ASD and microbiota composition alteration and warrants additional prospective cohort studies to evaluate associations of the bacterial changes with ASD symptoms, which would provide further evidence for precise microbiological treatment of ASD.